2004
DOI: 10.1080/20786204.2004.10873095
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical ultrasound training of and practise by general practitioners in the private sector, Free State

Abstract: Background:The aim of the study was to determine the level of obstetrical ultrasound training and practice of general practitioners in the Free State private sector. Methods:In this descriptive study, questionnaires were mailed to all general practitioners in the Free State private sector. The questionnaire included demographic information about the practitioner, the ultrasound profile of the practice, and the type of machine used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The theoretical and practical training provided to the health professionals who perform prenatal scans in Africa is generally low-quality. 10 As we know, ultrasound is an operator-dependent technique where the results depend crucially on the sonographer's knowledge and experience. As we can see on Table 2, most of today's practitioners are not sufficiently As can be seen, countries in North Africa (Morocco, Algeria, Tunisia, Egypt, etc.)…”
Section: Sonographer Trainingmentioning
confidence: 99%
“…The theoretical and practical training provided to the health professionals who perform prenatal scans in Africa is generally low-quality. 10 As we know, ultrasound is an operator-dependent technique where the results depend crucially on the sonographer's knowledge and experience. As we can see on Table 2, most of today's practitioners are not sufficiently As can be seen, countries in North Africa (Morocco, Algeria, Tunisia, Egypt, etc.)…”
Section: Sonographer Trainingmentioning
confidence: 99%
“…Moreover, the ultrasound procedure is relatively easy, misuse by physicians without adequate training is possible which, unfortunately, and common produce missed diagnoses of gross abnormalities and incorrect treatment of patients. 2 From the other side, the patient is intensely involved in the ultrasound examination and has the right to know the level of qualification of the physician who perform the ultrasound scan and the board level of institution where the scan is performed.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that only 18.6% of ultrasound practitioners had training in their postgraduate studies (MFamMed 5, Diploma 3) [16]. Another study reported that 40.4% of operators have short course in theory only, 38.3% of sonographers have no training at all, and only 14.9% have attended practical courses, of whom only 2.1% were carried out in a hospital environment [9].…”
Section: The Way Forwardmentioning
confidence: 99%
“…It is not only the availability but also the quality of ultrasound machines in use that influence the reliability and accuracy of ultrasound service provision. A study in South Africa revealed that 42% of the machines in use were bought more than 5 years before the survey and one machine was bought 16 years ago [16]. The age of the machine plays a definite role in the quality of ultrasound investigations as ultrasound machine technology progresses constantly [16].…”
Section: The Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation